IMPLEMENTATION OF ISLAMIC VALUES IN THE EDUCATION CURRICULUM IN INDONESIA - Nasution, Nasution (PT Altin Riset Publishing, 2024)
This study aims to analyze the implementation of Islamic values in the education curriculum in Indonesia and identify challenges and strategies to improve the effectiveness of the integration of these values. This research uses a descriptive qualitative method with data collection techniques through interviews, participant observation, and analysis of curriculum documents at various levels of education, such as elementary schools, junior high schools, senior high schools, and madrasah. The results showed that Islamic values have been integrated through Islamic Religious Education (PAI) subjects, religion-based extracurricular activities, and daily habituation in the school environment. Values such as honesty, discipline, responsibility, and social care are taught with various approaches, including storytelling, discussion, and hands-on practice methods. However, this study also found some challenges, such as limited learning time, varied teacher competencies, and the influence of technology and the social environment. To overcome these challenges, the proposed strategies include teacher competency training, a more integrative curriculum update, strengthening extracurricular activities, and increasing collaboration between schools, parents, and communities. With the implementation of these strategies, education in Indonesia is expected to be able to produce a generation that is not only academically superior but also has a strong Islamic character as a provision in facing global challenges.